Universidad Mayor de San Marcos and the Universitary During and After the War with Chile - Buenaño Olivo, Julio (2010)
Did the Universidad Mayor de San Marcos and San Marcos’s people took part directly in the war with Chile in 1879? If they did, how? Why the official history and the institutional history have silenced such participation? Did the University of San Marcos and San Marcos’s people deserve to die on the ingratitude and forgetfulness? This paper deals with the questions at issue.